The Role of Project Human Resource Management in the Industrial Sector in the UAE - BUYAKOVICH, OLGA (2018)
Project human resource management is gaining popularity among scholars as they try to investigate its relevance in enhancing the success of a firm, especially those operating in highly competitive industries. The study focused on investigating the role of project human resource management in the United Arab Emirates’ industrial sector. The data is collected from primary and secondary sources. The outcome of the study shows that there is a close relationship between effective project human resource management and the success of a company. An organization that understands how to manage its resources is capable of improving efficiency in operation. The competitive business environment is forcing many companies around the world to change the mode of their operations. Large tasks, such as the development of new products, are now conducted as a project. It means that instead of operating per department, as has always been the norm, the new task will be assigned to a specific team and a given amount of resources to work within a given time. The traditional approach made it impossible to track down the unit cost of operations and the real value obtained from a new product. However, this new approach makes it easy to have a clear understanding of the value of each new idea that is developed into a product or a strategy within the firm. The management will know the specific resources and employees assigned the task and the value realized out of it. When a project is undertaken, it is easy to evaluate areas of strength and weaknesses of the assigned team. The management will develop with ways of addressing such weaknesses to enhance the success of future projects. When different companies experience improved performance, the industry’s performance will also improve.